Exploring the barriers and facilitators to safer hair product purchasing and use among Black women in the greater Boston area through photovoice in the RESTYLE study - Marissa Chan; Marlee R. Quinn; Jackeline Morales; Cynthia Jones; Cynthia Jones; Kalya Murray; Gary Adamkiewicz; Leopoldo J. Cabassa; Leopoldo J. Cabassa; Tamarra James-Todd; Tamarra James-Todd (Frontiers in Public Health)
IntroductionRacial/ethnic differences in personal care product (PCP) use, including hair products, are well-documented in the United States (US). Black women are more highly exposed to endocrine disrupting chemicals in PCPs compared to other racial/ethnic groups. We identified barriers and facilitators to safer hair product purchasing and use in the greater Boston, Massachusetts area.MethodsTwenty-one Black women were recruited through community organizations to participate in photovoice as a part of the Retail Environment and Hair Styling Exposure (RESTYLE) study. Participants as co-researchers were trained in photography/PCP safety preceding a focus group. The co-researchers took photographs based on a prompt and then engaged in an interview and a focus group to discuss the photos. The co-researchers participated in another round of photography, interviews, and focus groups based on a second co-developed prompt. All study activities were virtual. Deductive and inductive approaches were used to code and analyze the data using NVIVO Version R1.ResultsFive themes related to barriers were identified (e.g., unsafe ingredients allowed in US products and differences in access to safer hair products). Two concepts underlying the barriers were distrust in government/large corporations and individual burden/responsibility to shop for safer products. The two themes related to facilitators were going back to our cultural and community roots and raising individual knowledge and public awareness for action.DiscussionPhotovoice is a powerful community-based participatory method rooted in community experiences. Several barriers and facilitators to safer hair product purchasing and use were identified among the co-researchers’ lived experiences that can inform future research and interventions.